The Length of Schooling and the Timing of Family Formation - Jan Marcus (CESifo Economic Studies, 2022)
Individuals typically traverse several life phases before forming a family. We analyze whether changing the duration of one of these phases, the education phase, affects the timing of marriage and childbearing. For this purpose, we exploit the introduction of short school years (SSYs) in Germany in 1966–1967, which compressed the education phase without affecting the curriculum. Based on difference-in-differences regressions and German Micro Census data, we find that SSY exposure affects the timing of marriage for individuals in all secondary school tracks and shifts forward the birth of the first child mainly for academic-track graduates. This highlights that education policies might not only affect family formation through human capital accumulation, but also through changing the duration of earlier life phases. This is important as not only age at marriage and first birth increases in many countries, but also the duration of the education phase. (JEL codes: I26, J12, J13, J24)
Keywords: I26; J12; J13; J24; 330; Family formation; instruction time; fertility; marriage